1987
DOI: 10.1111/j.1471-4159.1987.tb05635.x
|View full text |Cite
|
Sign up to set email alerts
|

Synaptosomal Uptake and Release of Dopamine in Rat Striatum After Hypoxia

Abstract: Hypoxia induces alterations of central monoaminergic transmission and of behavior. We studied the effect of hypoxia on adult and newborn rats to obtain more information about long-lasting changes of dopamine (DA) transmission caused by neonatal hypoxia. One single exposure of adult rats to hypoxia leads to short-term alterations of DA uptake: decreased affinity of the uptake carrier to DA (Km, 269.5% versus control) and a sharp increase of Vmax up to 301.4% resulting in an increase of total uptake of DA into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
3

Year Published

1992
1992
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
3
3
Order By: Relevance
“…The reports from literature concerning the effects of hypoxia on DA uptake are contradictory: decreased (Pastuszko et al, 1982) and increased (Freemann and Gibson, 1986;Odarjuk etal., 1987) DA uptakes have been reported. The findings reported in Table 3 seem to be in contrast to previous data (Odarjuk et al, 1987) when an increased high-affinity uptake was found after a 12 hour hypoxia. At that time we determined the uptake kinetics by using only 4 DA concentrations between 0.021aM and 0.1 gM and a Michaelis Menten model.…”
Section: Discussioncontrasting
confidence: 86%
“…The reports from literature concerning the effects of hypoxia on DA uptake are contradictory: decreased (Pastuszko et al, 1982) and increased (Freemann and Gibson, 1986;Odarjuk etal., 1987) DA uptakes have been reported. The findings reported in Table 3 seem to be in contrast to previous data (Odarjuk et al, 1987) when an increased high-affinity uptake was found after a 12 hour hypoxia. At that time we determined the uptake kinetics by using only 4 DA concentrations between 0.021aM and 0.1 gM and a Michaelis Menten model.…”
Section: Discussioncontrasting
confidence: 86%
“…That the high-affinity uptake kinetics remained unchanged in our experiments is in contrast to previous findings of Odarjuk et al (1987). Employing the same type of hypoxia these authors described a threefold increased V,,,axl whereas we observed an insignificant elevation of about 30%.…”
Section: Discussioncontrasting
confidence: 57%
“…So far, only the effects of hypoxia directed to the high-affinity uptake have been studied. The results of these investigations are conflicting with decreased (Pastuszko et al, 1982;Saijoh et al, 1985), increased (Freeman and Gibson, 1986;Odarjuk et al, 1987), andunchanged (Wustmann, 1984;Freeman and Gibson, 1986) uptake having been reported.…”
Section: Introductioncontrasting
confidence: 45%
See 2 more Smart Citations